INTEGRASI PENGEMBANGAN SUMBERDAYA MANUSIA (SDM) DAN TEKNOLOGI BUDIDAYA ORGANISME AKUATIK LAUT TEPAT GUNA TERPADU DI KABUPATEN KEPAULAUAN SELAYAR, SULAWESI SELATAN - Vinasyiam, Apriana; Effendi, Irzal; Budiardi, Tatag; Diatin, Iis; Hadiroseyani, Yani; Astari, Belinda (Universitas Mataram, 2025)
The production of fisheries cultivation in Selayar Islands Regency has obstacles, including lack of technology, disease attacks, and not yet mastered marketing strategies and sales of production results. This is the background for implementing the integration of human resource development (HRD) and integrated appropriate marine aquatic organism cultivation technology in Selayar Islands Regency, South Sulawesi. This activity aims to increase human resources' capacity in aquatic organism cultivation through training and mentoring activities. The community service program consists of maritime development training through fish cultivation, hybrid public lectures on potential and challenges in mariculture, discussions on program sustainability/exploration of cooperation with the Fisheries Service and Regional Secretary, and visits and consultations on community ponds. Maritime development training through fish cultivation uses materials on container preparation, cultivation systems, feed and feeding, water quality management, and fish and shrimp health management. Public lectures on potential and challenges in mariculture are carried out using materials on fish cultivation in KJA, lobster cultivation, and marketing of mariculture products. The partner stakeholders include IPB, the Fisheries Service of Selayar Islands Regency, UNHAS (TP3 Selayar Study Program), fisheries extension workers (KKP), and fish farming groups.